Penerapan Pendidikan Matematika Realistik Indonesia (PMRI) untuk Meningkatkan Hasil Belajar Matematika Materi Pecahan Senilai pada Siswa Kelas IV SDN Jelambar Baru 01 - Astri Anggita Putri; Alberth Supriyanto Manurung (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This research is motivated by the problems that occur in fourth grade students of Jelambar Baru 01 Elementary School, namely there are students who still have difficulty answering math questions because the acquisition of learning outcomes and student learning completeness is still low. Of the 28 students, there were only 8 students who scored above the minimum completeness criteria (KKM), while the other 20 students scored below the minimum completeness criteria (KKM), so there were more students who had not completed than the students who had already completed. This happens because during learning activities, the teacher only uses the lecture method which makes it difficult for students to understand the material because the material is abstract for students. To solve this problem, the application of realistic mathematics is used to make the subject matter more concrete. This research uses Classroom Action Research (CAR). The purpose of this study is to improve student learning outcomes. The results of this study indicate an increase in student learning outcomes as seen from the acquisition of the percentage of completeness in the first cycle of 60.71%, while in the second cycle the percentage of completeness increased to 85.71%. Then the increase that occurs from cycle I to cycle II is 25%.